Political corruption through misappropriation of covid-19 funds and reliefs in Nigeria (2020)
The year 2020 remains a year cast in global history for the sudden onset of a deadly disease which shut down nations of the world and imposed huge economic effects. The Covid-19 pandemic predisposed many countries, including Nigeria, to splurges in public spending to alleviate economic hardship imposed by the pandemic. Consequently, allegations of political corruption and misuse of public funds was rife in the political landscape. Over 1 billion dollars was allegedly drawn from both external and foreign sources for government spending towards Covid-19 pandemic mitigation funds. By late 2020, social media platforms such as Twitter and Facebook became awash with gory stories of hoarded and fraudulently converted relief materials by political and public leaders. While Nigeria has an established legal framework in combating corruption generally, it has been shown by previous studies that the legal framework has not achieved much in combating the menace of corruption from a legal standpoint. Much of the existing legal framework is reactive rather than proactive. With respect to Covid-19 response funds, emergency assistance loan to the government from international financial institutions such as the International Monetary Fund (IMF) was conditioned upon certain terms such as external and periodic audit to forestall the possibility of misappropriation and corruption. It remains to be known how far effective the terms have been. Given the nature of the allegations of corruption, would the existing legal framework apprehend the dimension of political corruption elicited by Covid-19 pandemic? This paper examines the subject of political corruption in Nigeria within the context of Covid-19 pandemic. It adopts a purely doctrinal and desktop legal research approach in analysing the existing laws on corruption and the emerging dimensions of political corruption introduced by Covid-19 induced public corruption. It proposes a more proactive approach to the subject of political corruption in Nigeria through accountability and transparency in public spending and non-legal approach which incorporates the role of non-governmental organisations.